Characterization of nimesulide and development of immediate release tablets - Antunes Rocha, Helvécio Vinícius; Augusto, Rachel de Sousa; Prado, Livia Deris; de Carvalho, Erika Martins (Eclética Química, 2019)
This paper aims to characterize nimesulide raw materials from different manufacturers and to develop immediate release tablets, in order to register a generic product. Also, raw material characteristics and the tablets final properties were investigated in order to establish a different specification for quality control. Two micronized and one non-micronized nimesulide samples were obtained from different manufacturers and were characterized by thermal analysis, spectroscopic techniques, morphological analysis, flowability and biopharmaceutical evaluation. The samples belong to the same polymorph. The formulations design and the choice of the production process were carried out based on the results obtained in the characterization assessments. The proposed formulations showed different dissolution behavior. One formulation was selected and then the dissolution was evaluated in different dissolution media containing varying concentrations of surfactant, in order to verify if the concentration of 2% (v/v) of polysorbate 80, recommended by the Brazilian Pharmacopoeia, would be overestimating the bioavailability of the drug. The results showed that the percentage of surfactant present in the dissolution medium directly impacts the amount of dissolved drug. The selected formulation demonstrated promising results to proceed with the bio batches manufacture and the pharmaceutical equivalence study.